2014
DOI: 10.1016/j.ajpath.2014.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Healing via Periosteal Callus Formation Requires Macrophages for Both Initiation and Progression of Early Endochondral Ossification

Abstract: The distribution, phenotype, and requirement of macrophages for fracture-associated inflammation and/or early anabolic progression during endochondral callus formation were investigated. A murine femoral fracture model [internally fixed using a flexible plate (MouseFix)] was used to facilitate reproducible fracture reduction. IHC demonstrated that inflammatory macrophages (F4/80(+)Mac-2(+)) were localized with initiating chondrification centers and persisted within granulation tissue at the expanding soft call… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
253
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(271 citation statements)
references
References 69 publications
(79 reference statements)
13
253
0
5
Order By: Relevance
“…Monocytes differentiate into macrophages, which appear to control each subsequent phase of tissue repair to ensure successful progression through the healing process. 4 Although the mechanisms by which macrophages modulate healing are poorly understood, the critical role of macrophages in tissue repair has been repeatedly demonstrated by pharmacologic or genetic depletion of macrophages, which reduces or delays healing in many tissues, including skin, 5 muscle, 6 liver, 7 bone, 8,9 and cardiac tissue. 10 A landmark study by Godwin et al 11 showed that macrophage depletion reduced limb regeneration in the salamander, which otherwise has a massive regenerative capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Monocytes differentiate into macrophages, which appear to control each subsequent phase of tissue repair to ensure successful progression through the healing process. 4 Although the mechanisms by which macrophages modulate healing are poorly understood, the critical role of macrophages in tissue repair has been repeatedly demonstrated by pharmacologic or genetic depletion of macrophages, which reduces or delays healing in many tissues, including skin, 5 muscle, 6 liver, 7 bone, 8,9 and cardiac tissue. 10 A landmark study by Godwin et al 11 showed that macrophage depletion reduced limb regeneration in the salamander, which otherwise has a massive regenerative capacity.…”
Section: Introductionmentioning
confidence: 99%
“…This is a clear message that endochondral ossification was severely disturbed in mice without sufficient macrophages. A similar failure of bone reconstruction was observed by Raggatt's research group (Raggatt et al, 2014). They created transgenic mice, in which mature myeloid cells carried a Fas-based suicide gene.…”
Section: Fracture Healingmentioning
confidence: 65%
“…Es un proceso complejo que involucra una interacción coordinada entre varias líneas celulares, factores de crecimiento y componentes de la matriz extracelular (Claes et al, 2012;Raggatt et al, 2014). Por otro lado en la reparación, el tejido que se forma es un tejido cicatricial, con características diferentes al original (Córdova, 2010).…”
unclassified
“…Además se ha demostrado la presencia de macrofagocitos durante esta fase tanto en humanos (Andrew et al, 1994;Oni, 1997), como en animales (Hankemeier et al, 2001;Alexander et al, 2011;Raggatt et al). Fig.…”
unclassified